LEGAL PROTECTION OF UNDERAGE WORKERS FROM THE VIEWPOINT OF CHILDREN'S RIGHTS IN INDONESIA - Hanifah, Ida (Proceeding International Seminar of Islamic Studies, 2024)
Described in Law Number 13 of 2003 concerning Employment of minors is explained in Article 1 paragraph 26